A new species of Lycodon Fitzinger, 1826 from the Northern part of the Truong Son Mountains, Central Vietnam (Reptilia, Squamata, Colubridae) - Nguyen, Tan Van; Vogel, Gernot (Zootaxa, 2025)
A new species of the genus Lycodon is described based on four specimens collected from the Phong Nha-Ke Bang National Park and Dong Chau-Khe Nuoc Trong Nature Reserve, Quang Binh Province, Central Vietnam. Lycodon poyarkovi sp. nov. is superficially similar to L. paucifasciatus Rendahl in Smith, but can be distinguished from the latter by the following characters: higher number of ventral scales in males, higher number of subcaudal scales in females, higher number of crossbands on body and tail, by having a lower number of ventral scales before the first crossband starts, and by having lower numbers of vertebrals covered by the first crossband. The new species seems to be endemic to the northern part of Truong Son Mountains, the Ben Hai River, which is considered an important biogeographic barrier between Lycodon poyarkovi sp. nov. and L. paucifasciatus. We suggest that the new species should be considered as Least Concerned (LC) following the IUCN’s Red List categories. Further studies reassessing the taxonomic status of Lycodon anakradaya and L. cardamomensis are required.